Recent advances in single molecule magnetism of dysprosium-metallofullerenes. Issue 9 (13th February 2019) - Spree, Lukas; Popov, Alexey A.
Abstract : Encapsulation of dysprosium ions in fullerenes results in efficient air stable single molecule magnets, which can be used in preparation of various 1D, 2D, and 3D assemblies. Abstract : This article outlines the magnetic properties of single molecule magnets based on Dy-encapsulating endohedral metallofullerenes. The factors that govern these properties, such as the influence of different non-metal species in clusterfullerenes, the cage size, and cage isomerism are discussed, as well as the recent successful isolation of dimetallofullerenes with unprecedented magnetic properties. Finally, recent advances towards the organization of endohedral metallofullerenes in 1D, 2D, and 3D ordered structures with potential for devices are reviewed.